Multilayer optical film and method of making same
A multilayer optical film with specific resin compositions and controlled stretching addresses production challenges, achieving high heat and solvent resistance along with improved quality and optical performance.
Patent Information
- Application Number
- JP2021158041
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-09-28
AI Technical Summary
Existing multilayer optical films face challenges in producing high-quality products due to issues such as uneven thickness and breakage during the stretching process, particularly when using core layers with high glass transition temperatures and crystalline polymers, which affect heat and solvent resistance.
A multilayer optical film design comprising a pair of surface layers (B layers) and a core layer (A layer) using specific resin compositions: an amorphous polymer (a) without a melting point and a resin (b) containing a crystalline polymer (b1) and amorphous polymer (b2), with defined glass transition and cold crystallization temperatures, ensuring close contact and controlled stretching at or above the glass transition temperature of the amorphous polymer.
The solution enables the production of high-quality optical films with enhanced heat and solvent resistance, reduced thickness unevenness, and improved interlayer adhesion, while maintaining desired optical properties like birefringence and retardation.
Smart Images

Figure 0007615993000002 
Figure 0007615993000003 
Figure 0007615993000001
Abstract
Description
[Technical field]
[0001] The present invention relates to multilayer optical films and methods for making same. [Background technology]
[0002] Conventionally, films for optical applications have generally been produced from amorphous polymers. However, amorphous polymers tend to have poor solvent resistance. Therefore, it has been proposed to produce a film with excellent solvent resistance by using a resin containing a combination of an amorphous polymer and a crystalline polymer (for example, Patent Documents 1 and 2). In addition, a multilayer optical film combining such a film with another film has also been proposed (for example, Patent Documents 3 and 4). In such a multilayer optical film, by adopting a layer containing a crystalline polymer as a layer constituting the surface layer, it is expected that the solvent resistance can be improved and the core layer between them can exhibit the desired optical performance. The core layer can be, for example, a retardation layer having a retardation exhibited by stretching. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-249645 A [Patent Document 2] JP 2007-016102 A [Patent Document 3] Patent Application No. 3-230614 [Patent Document 4] International Publication No. 2013 / 069666 Summary of the Invention [Problem to be solved by the invention]
[0004] The core layer that exhibits optical performance is required to have a high glass transition temperature in order to enhance the heat resistance of the optical film when it is used. Such a core layer is required to be stretched at a relatively high temperature during the stretching process. However, when an optical film is produced using such a core layer having a high glass transition temperature together with a surface layer containing a crystalline polymer, it is difficult to easily produce a high-quality product. For example, there is a high tendency for defects to occur, such as thickness unevenness occurring on a cooling roll when a resin is formed into a film by melt extrusion, and breakage occurring when the pre-stretched film is subjected to a stretching process.
[0005] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a multilayer optical film that has high heat resistance during use, high solvent resistance, and can be easily produced to a high quality, and a method for producing the same. [Means for solving the problem]
[0006] The present inventors have conducted studies to solve the above problems, and as a result, have found that the above problems can be solved by using a material that has specific properties in relation to a core layer as a material constituting a surface layer of a multilayer optical film, and have completed the present invention. That is, the present invention includes the following.
[0007] [1] A multilayer optical film comprising a pair of B layers constituting surface layers on the front and back surfaces, and an A layer located between the pair of B layers, The layer A is a layer of a resin (a) containing an amorphous polymer (a) having no melting point, the layer B is a layer of a resin (b) having a melting point, the layer comprising a crystalline polymer (b1) having a melting point and an amorphous polymer (b2) having no melting point; The resin (a) and the resin (b) satisfy the following formulas (1) to (3): TgA-TgB≦20℃ (1) 110℃ <TgB<140℃ (2) 180℃ <TcB<235℃ (3) In the formula, TgA is the glass transition temperature of resin (a), TgB is the glass transition temperature of resin (b), and TcB is the cold crystallization temperature of resin (b). Multilayer optical films. [2] The multilayer optical film according to [1], wherein the A layer and the B layer are in interlayer adhesion. [3] The multilayer optical film according to [1] or [2], wherein each of the layers B has a thickness of 10 μm or less. [4] The multilayer optical film according to any one of [1] to [3], having a haze of 1% or less. [5] A method for producing the multilayer optical film according to any one of [1] to [4], preparing the resin (a) and the resin (b); A production method comprising a step of forming the resin (a) and the resin (b) to obtain a multilayer resin film. [6] The method for producing a multilayer optical film according to [5], further comprising a step of stretching the multilayer resin film at a stretching temperature of TgA or higher. Effect of the Invention
[0008] According to the present invention, there are provided a multilayer optical film that has high heat resistance during use, high solvent resistance, and can be easily produced with high quality, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a side view that illustrates a method for testing solvent resistance in the present examples. [Diagram 2] FIG. 2 is a perspective view that illustrates a method for testing interphase adhesion in the present examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0011] In the following description, a "long" film refers to a film having a length of 5 times or more, preferably 10 times or more, the width, specifically a film having a length that can be wound into a roll for storage or transportation. There is no particular upper limit to the length of the film, and it can be, for example, 100,000 times or less the width.
[0012] In the following description, the in-plane retardation Re is a value expressed by Re=(nx-ny)×d unless otherwise specified. Furthermore, the retardation Rth in the thickness direction is a value expressed by Rth=[{(nx+ny) / 2}-nz]×d unless otherwise specified. Furthermore, the birefringence Δn is a value expressed by nx-ny unless otherwise specified, and therefore is a value expressed by Re / d. Here, nx represents the refractive index in the direction perpendicular to the thickness direction (in-plane direction) that gives the maximum refractive index. ny represents the refractive index in the in-plane direction that is perpendicular to the direction of nx. nz represents the refractive index in the thickness direction. d represents the thickness. The measurement wavelength is 590 nm unless otherwise specified.
[0013] In the following description, unless otherwise specified, a polymer having positive intrinsic birefringence means a polymer whose refractive index in the stretching direction is greater than that in the direction perpendicular thereto, and a polymer having negative intrinsic birefringence means a polymer whose refractive index in the stretching direction is smaller than that in the direction perpendicular thereto.
[0014] [Multilayer Optical Films: Overview] The multilayer optical film of the present invention comprises a pair of layers B constituting the front and back surface layers, and a layer A located therebetween. Here, when one surface of layer B that is the surface layer of the multilayer optical film is defined as the front surface, the other surface of the surface layers is defined as the back surface. Layer A is a layer of resin (a) containing an amorphous polymer (a) having no melting point, and may be a layer consisting only of resin (a), while layer B is a layer of resin (b) having a melting point, containing a crystalline polymer (b1) having a melting point and an amorphous polymer (b2) having no melting point, and may be a layer consisting only of resin (b).
[0015] [Resin (b): Crystalline polymer (b1)] As the crystalline polymer (b1), various crystalline polymers, including known ones, can be used. In general, a crystalline polymer is a polymer having crystallinity. A polymer having crystallinity is a polymer having a melting point. The melting point of a polymer can be measured by a differential scanning calorimeter (DSC). Thus, a crystalline polymer is a polymer whose melting point can be observed by a differential scanning calorimeter (DSC).
[0016] The crystalline polymer (b1) may have a positive intrinsic birefringence or a negative intrinsic birefringence. Among them, a crystalline polymer having a positive intrinsic birefringence is preferred.
[0017] Examples of the crystalline polymer (b1) include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); polyolefins such as polyethylene (PE) and polypropylene (PP); and cyclic olefin polymers are preferred. That is, the crystalline polymer (b1) is preferably a cyclic olefin polymer having a melting point. Hereinafter, a cyclic olefin polymer having a melting point may be referred to as a "cyclic olefin crystalline polymer".
[0018] The cyclic olefin-based crystalline polymer may have an alicyclic structure in its molecule. Such a cyclic olefin-based crystalline polymer may be, for example, a polymer obtained by polymerization reaction using a cyclic olefin as a monomer, or a hydrogenated product thereof. When using the resin (b) containing the cyclic olefin-based crystalline polymer, the mechanical properties, heat resistance, transparency, low moisture absorption, dimensional stability and light weight of the multilayer optical film can be improved.
[0019] Examples of the alicyclic structure include a cycloalkane structure and a cycloalkene structure. Among these, the cycloalkane structure is preferred because it is easy to obtain a multilayer optical film having excellent properties such as thermal stability. The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. When the number of carbon atoms contained in one alicyclic structure is within the above range, the mechanical strength, heat resistance, and moldability are highly balanced.
[0020] In the cyclic olefin crystalline polymer, the ratio of the structural unit having alicyclic structure to all structural units is preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. When the ratio of the structural unit having alicyclic structure is high as described above, heat resistance can be improved. The ratio of the structural unit having alicyclic structure to all structural units can be 100% by weight or less. In addition, in the cyclic olefin crystalline polymer, the remainder other than the structural unit having alicyclic structure is not particularly limited, and can be appropriately selected according to the purpose of use.
[0021] Examples of the cyclic olefin-based crystalline polymer include the following polymer (α) to polymer (δ): Among these, polymer (β) is preferred because a multilayer optical film having excellent heat resistance can be easily obtained from it. Polymer (α): A ring-opening polymer of a cyclic olefin monomer, which has crystallinity. Polymer (β): A hydrogenated product of polymer (α) and has crystallinity. Polymer (γ): An addition polymer of a cyclic olefin monomer, which has crystallinity. Polymer (δ): A hydrogenated polymer (γ) having crystallinity.
[0022] Specifically, the crystalline polymer containing an alicyclic structure is preferably a dicyclopentadiene ring-opening polymer having crystallinity, and a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity. Among them, a dicyclopentadiene ring-opening polymer hydrogenation product having crystallinity is particularly preferred. Here, the dicyclopentadiene ring-opening polymer refers to a polymer in which the ratio of dicyclopentadiene-derived structural units to all structural units is usually 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 100% by weight.
[0023] The hydrogenated ring-opening polymer of dicyclopentadiene preferably has a high ratio of racemo dyads. Specifically, the ratio of racemo dyads in the repeating units of the hydrogenated ring-opening polymer of dicyclopentadiene is preferably 51% or more, more preferably 70% or more, and particularly preferably 85% or more. A high ratio of racemo dyads indicates high syndiotactic stereoregularity. Therefore, the higher the ratio of racemo dyads, the higher the melting point of the hydrogenated ring-opening polymer of dicyclopentadiene tends to be. The ratio of racemo-dyads is described in the Examples below. 13 It can be determined based on C-NMR spectrum analysis.
[0024] As the polymer (α) to polymer (δ), polymers obtained by the production method disclosed in WO 2018 / 062067 can be used.
[0025] The melting point Tmb1 of the crystalline polymer (b1) is preferably 200° C. or higher, more preferably 230° C. or higher, and preferably 290° C. or lower. When a crystalline polymer (b1) having such a melting point Tmb1 is used, a multilayer optical film having an even better balance between formability and heat resistance can be obtained.
[0026] The crystalline polymer (b1) usually has a glass transition temperature Tgb1. The specific glass transition temperature Tgb1 of the crystalline polymer (b1) is not particularly limited, but is usually 85°C or higher and usually 170°C or lower.
[0027] The glass transition temperature and melting point of a polymer can be measured by the following method. First, the polymer is melted by heating, and the melted polymer is quenched with dry ice. Then, using this polymer as a test specimen, the glass transition temperature and melting point of the polymer can be measured with a differential scanning calorimeter (DSC) at a heating rate of 10° C. / min (heating mode).
[0028] The weight average molecular weight (Mw) of the crystalline polymer (b1) is preferably 1,000 or more, more preferably 2,000 or more, and is preferably 1,000,000 or less, more preferably 500,000 or less. The crystalline polymer (b1) having such a weight average molecular weight has an excellent balance between moldability and heat resistance.
[0029] The molecular weight distribution (Mw / Mn) of the crystalline polymer (b1) is preferably 1.0 or more, more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less. Here, Mn represents the number average molecular weight. The crystalline polymer (b1) having such a molecular weight distribution has excellent moldability.
[0030] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer can be measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a developing solvent. If the polymer does not dissolve in cyclohexane, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) can be measured in terms of polyisoprene using toluene as a solvent.
[0031] The crystalline polymer (b1) may be used alone or in combination of two or more kinds in any ratio.
[0032] The amount of the crystalline polymer (b1) contained in the resin (b) is preferably 30% by weight or more, more preferably 35% by weight or more, particularly preferably 40% by weight or more, and is preferably 80% by weight or less, more preferably 75% by weight or less, particularly preferably 70% by weight or less, based on 100% by weight of the resin (b). When the amount of the crystalline polymer (b1) is within the above range, the solvent resistance, heat resistance, and flexibility of the multilayer optical film can be effectively improved.
[0033] The weight ratio Wa / Wb of the amount Wa of the crystalline polymer (b1) and the amount Wb of the amorphous polymer (b2) contained in the resin (b) is preferably within a specific range. Specifically, the weight ratio Wa / Wb is preferably greater than 30 / 70, more preferably greater than 35 / 65, particularly preferably greater than 40 / 60, and preferably less than 80 / 20, more preferably less than 75 / 25. By setting the weight ratio Wa / Wb to the lower limit or more, the resin (b) can be a resin having a melting point. In addition, when the weight ratio Wa / Wb is within the above range, the solvent resistance, heat resistance, and flexibility of the multilayer optical film can be effectively improved.
[0034] The total amount of the crystalline polymer (b1) and the amorphous polymer (b2) contained in the resin (b) is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 80% by weight to 100% by weight, still more preferably 90% by weight to 100% by weight, and particularly preferably 95% by weight to 100% by weight, based on 100% by weight of the resin (b).
[0035] [Resin (b): Amorphous polymer (b2)] As the amorphous polymer (b2), various amorphous polymers, including known ones, can be used. In general, an amorphous polymer is a polymer that does not have crystallinity. A polymer that does not have crystallinity is a polymer that does not have a melting point. Therefore, an amorphous polymer refers to a polymer whose melting point cannot be observed by a differential scanning calorimeter (DSC).
[0036] The amorphous polymer (b2) may have a positive intrinsic birefringence or a negative intrinsic birefringence. Among them, an amorphous polymer having a positive intrinsic birefringence is preferred.
[0037] The amorphous polymer (b2) is preferably a cyclic olefin polymer. That is, the amorphous polymer (b2) is preferably a cyclic olefin polymer that does not have a melting point. Hereinafter, a cyclic olefin polymer that does not have a melting point may be referred to as a "cyclic olefin amorphous polymer." A cyclic olefin amorphous polymer is excellent in mechanical properties, heat resistance, transparency, low moisture absorption, dimensional stability, and light weight.
[0038] The cyclic olefin-based amorphous polymer may have a cyclic structure in its molecule. Usually, the structural unit of the cyclic olefin-based amorphous polymer has an alicyclic structure. The cyclic olefin-based amorphous polymer may be a polymer having an alicyclic structure in the main chain, a polymer having an alicyclic structure in the side chain, a polymer having an alicyclic structure in the main chain and in the side chain, or a mixture of two or more of these in any ratio. Among them, the cyclic olefin-based amorphous polymer preferably has an alicyclic structure in the main chain from the viewpoint of mechanical strength and heat resistance.
[0039] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structures and unsaturated alicyclic hydrocarbon (cycloalkene, cycloalkyne) structures. Among them, from the viewpoint of mechanical strength and heat resistance, cycloalkane structures and cycloalkene structures are preferred, and cycloalkane structures are particularly preferred.
[0040] The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, and preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. When the number of carbon atoms constituting the alicyclic structure is within this range, mechanical strength, heat resistance, and moldability are highly balanced.
[0041] In the cyclic olefin-based amorphous polymer, the ratio of the structural units having an alicyclic structure to all structural units is preferably 55% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the ratio of the structural units having an alicyclic structure to all structural units is within this range, the transparency and heat resistance are good.
[0042] Examples of the cyclic olefin-based amorphous polymer include norbornene-based polymers, monocyclic cyclic olefin-based polymers, cyclic conjugated diene-based polymers, vinyl alicyclic hydrocarbon-based polymers, and hydrogenated products thereof. Among these, norbornene-based polymers and hydrogenated products thereof have good moldability.
[0043] Examples of norbornene-based polymers and their hydrogenated products include ring-opening polymers of monomers having a norbornene structure and their hydrogenated products; addition polymers of monomers having a norbornene structure and their hydrogenated products. Examples of ring-opening polymers of monomers having a norbornene structure include ring-opening homopolymers of one type of monomer having a norbornene structure, ring-opening copolymers of two or more types of monomers having a norbornene structure, and ring-opening copolymers of a monomer having a norbornene structure and other monomers that can be copolymerized therewith. Examples of addition polymers of monomers having a norbornene structure include addition homopolymers of one type of monomer having a norbornene structure, addition copolymers of two or more types of monomers having a norbornene structure, and addition copolymers of a monomer having a norbornene structure and other monomers that can be copolymerized therewith. Examples of these polymers include polymers disclosed in, for example, JP 2002-321302 A and WO 2017 / 145718 A. Among these, a hydrogenated product of a ring-opening polymer of a monomer having a norbornene structure is particularly suitable from the standpoints of moldability, heat resistance, low moisture absorption, dimensional stability, lightweight property, and the like.
[0044] Examples of monomers having a norbornene structure include bicyclo[2.2.1]hept-2-ene (common name: norbornene), tricyclo[4.3.0.1 2,5 ]Deca-3,7-diene (common name: dicyclopentadiene), tetracyclo[4.4.0.1 2,5 .1 7,10]Dodec-3-ene (trivial name: tetracyclododecene), and other norbornene monomers that do not contain an aromatic ring structure; norbornene monomers that have an aromatic substituent, such as 5-phenyl-2-norbornene, 5-(4-methylphenyl)-2-norbornene, 5-(1-naphthyl)-2-norbornene, and 9-(2-norbornen-5-yl)-carbazole; 1,4-methano-1,4,4a,4b,5,8,8a,9a-octahydrofluorene, 1,4-methano-1,4,4a,9a-tetrahydrofluorene (trivial name: meth norbornene-based monomers containing a norbornene ring structure and an aromatic ring structure in a condensed polycyclic structure, such as 1,4-methano-1,4,4a,9a-tetrahydrofluorene, 1,4-methano-1,4,4a,9a-tetrahydrodibenzofuran, 1,4-methano-1,4,4a,9a-tetrahydrocarbazole, 1,4-methano-1,4,4a,9,9a,10-hexahydroanthracene, and 1,4-methano-1,4,4a,9,10,10a-hexahydrophenanthrene; as well as derivatives of these compounds (for example, those having a substituent on the ring).
[0045] Examples of the substituent include alkyl groups such as methyl, ethyl, propyl, and isopropyl groups; alkylidene groups; alkenyl groups; and polar groups. Examples of the polar group include heteroatoms and atomic groups having heteroatoms. Examples of the heteroatoms include oxygen atoms, nitrogen atoms, sulfur atoms, silicon atoms, and halogen atoms. Specific examples of the polar group include halogen groups such as fluoro, chloro, bromo, and iodine groups; carboxyl groups; carbonyloxycarbonyl groups; epoxy groups; hydroxy groups; oxy groups; alkoxy groups; ester groups; silanol groups; silyl groups; amino groups; nitrile groups; sulfone groups; cyano groups; amide groups; and imide groups. The number of the substituents may be 1 or 2 or more. The types of the two or more substituents may be the same or different. However, from the viewpoint of obtaining an amorphous resin having a low saturated water absorption rate and excellent moisture resistance, it is preferable that the norbornene monomer has a small amount of polar groups, and it is more preferable that the norbornene monomer has no polar groups.
[0046] Examples of cyclic olefin-based amorphous polymers by trade name include "ZEONEX" manufactured by Zeon Corporation; "ARTON" manufactured by JSR Corporation; "APEL" manufactured by Mitsui Chemicals, Inc.; and "TOPAS" manufactured by Polyplastics Co., Ltd.
[0047] The glass transition temperature Tgb2 of the amorphous polymer (b2) is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 110° C. or higher, and is preferably 200° C. or lower, more preferably 190° C. or lower, and even more preferably 180° C. or lower. When the glass transition temperature Tgb2 of the amorphous polymer (b2) is within the above range, both the solvent resistance and heat resistance of the multilayer optical film can be effectively improved. Also, the stretching process can usually be carried out smoothly.
[0048] The weight average molecular weight (Mw) of the amorphous polymer (b2) is preferably 10,000 or more, more preferably 15,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, particularly preferably 50,000 or less. When the weight average molecular weight is within the above range, the mechanical strength and moldability of the resin (b) are highly balanced.
[0049] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the amorphous polymer (b2) is preferably 1.2 or more, more preferably 1.5 or more, particularly preferably 1.8 or more, and is preferably 3.5 or less, more preferably 3.0 or less, particularly preferably 2.7 or less. When the molecular weight distribution is at least the lower limit of the above range, the productivity of the polymer can be increased and the production costs can be reduced. On the other hand, when it is at or below the upper limit, the amount of low molecular weight components is reduced, thereby suppressing relaxation during exposure to high temperatures and improving the stability of the multilayer optical film.
[0050] The amorphous polymer (b2) may be used alone or in combination of two or more kinds in any ratio.
[0051] The amount of the amorphous polymer (b2) contained in the resin (b) is preferably 20% by weight or more, more preferably 25% by weight or more, particularly preferably 30% by weight or more, and is preferably 70% by weight or less, more preferably 65% by weight or less, particularly preferably 60% by weight or less, based on 100% by weight of the resin (b). When the amount of the amorphous polymer (b2) is within the above range, both the solvent resistance and heat resistance of the multilayer optical film can be effectively increased.
[0052] The glass transition temperature Tgb2 of the amorphous polymer (b2) is preferably relatively higher than the glass transition temperature Tgb1 of the crystalline polymer (b1). In general, the glass transition temperature of a crystalline polymer is low, while amorphous polymers have both high and low glass transition temperatures. Here, by adopting an amorphous polymer (b2) having a high glass transition temperature Tgb2, the glass transition temperature TgB of the resin (b) as a whole can be set to a desired high temperature.
[0053] The absolute value |Tgb1-Tgb2| of the difference between the glass transition temperature Tgb1 of the crystalline polymer (b1) and the glass transition temperature Tgb2 of the amorphous polymer (b2) is preferably in a specific range. Specifically, the absolute value |Tgb1-Tgb2| is preferably 30°C or more, more preferably 40°C or more, particularly preferably 50°C or more, and preferably 100°C or less, more preferably 90°C or less, particularly preferably 80°C or less. When the absolute value |Tgb1-Tgb2| is equal to or more than the lower limit, the glass transition temperature TgB of the resin (b) as a whole can be set to a desired high temperature. On the other hand, when the absolute value |Tgb1-Tgb2| is in the above range, the solvent resistance, heat resistance, and flexibility of the multilayer optical film can be effectively improved.
[0054] [Resin (b): optional component] The resin (b) may further contain an optional component in combination with the crystalline polymer (b1) and the amorphous polymer (b2). Examples of optional components include antioxidants such as phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants; light stabilizers such as hindered amine-based light stabilizers; waxes such as petroleum-based waxes, Fischer-Tropsch waxes, and polyalkylene waxes; nucleating agents such as sorbitol-based compounds, metal salts of organic phosphoric acids, metal salts of organic carboxylic acids, kaolin, and talc; fluorescent brightening agents such as diaminostilbene derivatives, coumarin derivatives, azole-based derivatives (e.g., benzoxazole derivatives, benzotriazole derivatives, benzimidazole derivatives, and benzothiazole derivatives), carbazole derivatives, pyridine derivatives, naphthalic acid derivatives, and imidazolone derivatives; ultraviolet absorbers such as benzophenone-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, and benzotriazole-based ultraviolet absorbers; colorants; flame retardants; flame retardant assistants; antistatic agents; plasticizers; near-infrared absorbers; lubricants; and inorganic fillers such as talc, silica, calcium carbonate, and glass fibers. The optional components may be used alone or in any combination of two or more at any ratio. The amount of the optional components may be appropriately determined within a range that does not significantly impair the effects of the present invention. The amount of the optional components may be within a range that allows the multilayer optical film to maintain a total light transmittance of 85% or more, for example.
[0055] [Characteristics of resin (b)] The resin (b) has a glass transition temperature TgB that satisfies the following formula (2). 110℃ <TgB<140℃ (2) Specifically, the glass transition temperature TgB of resin (b) is higher than 110°C, preferably higher than 115°C, particularly preferably 120°C or higher, and is lower than 140°C, preferably lower than 135°C, particularly preferably 130°C or lower.
[0056] The glass transition temperature TgB of the resin (b) can be adjusted, for example, by adjusting the type and amount of the crystalline polymer (b1) and the type and amount of the amorphous polymer (b2).
[0057] The glass transition temperature TgB of the resin (b) can be measured by the same method as the above-mentioned method for measuring the glass transition temperature of a polymer.
[0058] The resin (b) has a cold crystallization temperature TcB that satisfies the following formula (3). 180℃ <TcB<235℃ (3) In detail, the cold crystallization temperature TcB of the resin (b) is higher than 180°C, preferably higher than 185°C, particularly preferably 190°C or higher, and is usually lower than 235°C, preferably lower than 230°C, particularly preferably lower than 225°C.
[0059] The cold crystallization temperature TcB of the resin (b) can be adjusted, for example, by adjusting the type and amount of the crystalline polymer (b1) and the type and amount of the amorphous polymer (b2).
[0060] The cold crystallization temperature TcB of resin (b) can be measured by the following method. First, resin (b) is melted by heating, and the melted resin (b) is quenched with dry ice. Next, using this resin (b) as a test specimen, the cold crystallization temperature TcB of resin (b) can be measured at a heating rate of 10°C / min (heating mode) using a differential scanning calorimeter (DSC). In this measurement method, the cold crystallization temperature TcB can be obtained as the peak top temperature of the exothermic peak during the heating process.
[0061] When resin (b) has a glass transition temperature TgB that satisfies the above-mentioned formula (2) and a cold crystallization temperature TcB that satisfies the above-mentioned formula (3), the obtained multilayer optical film can have high solvent resistance and can suppress the occurrence of defects in the manufacturing process of the multilayer film.
[0062] The absolute value of the difference between the glass transition temperature TgB of the resin (b) and the glass transition temperature Tgb1 of the crystalline polymer (b1), |TgB-Tgb1|, is preferably in a specific range. Specifically, the absolute value |TgB-Tgb1| is preferably 3°C or more, more preferably 6°C or more, particularly preferably 10°C or more, and is preferably 45°C or less, more preferably 40°C or less, particularly preferably 35°C or less. When the absolute value |TgB-Tgb1| is in the above range, both the solvent resistance and heat resistance of the multilayer optical film can be effectively increased.
[0063] The absolute value |TgB-Tgb2| of the difference between the glass transition temperature TgB of the resin (b) and the glass transition temperature Tgb2 of the amorphous polymer (b2) is preferably in a specific range. Specifically, the absolute value |TgB-Tgb2| is preferably 20°C or more, more preferably 25°C or more, particularly preferably 30°C or more, and is preferably 80°C or less, more preferably 70°C or less, particularly preferably 60°C or less. When the absolute value |TgB-Tgb2| is in the above range, both the solvent resistance and heat resistance of the multilayer optical film can be effectively increased.
[0064] Resin (b) has a melting point Tmb. The melting point Tmb of resin (b) is preferably in the range of 200° C. or higher, more preferably 230° C. or higher, particularly preferably 240° C. or higher, and preferably 290° C. or lower. When resin (b) has a melting point Tmb in the above range, it is possible to effectively increase both the solvent resistance and heat resistance of the multilayer optical film.
[0065] The melting point Tmb of the resin (b) can be measured, for example, by the same method as the method for measuring the melting point of the polymer described above.
[0066] [B layer] Resin (b) in layer B may be in a crystallized state because it contains crystalline polymer (b1). However, resin (b) that satisfies desired requirements such as glass transition temperature TgB and is molded into the multilayer optical film of the present invention is often in an amorphous state in layer B. The presence or absence of crystallization can be determined by TEM observation under the conditions shown in the examples of the present application. When a spherulite structure or difference in contrast is found in the observed slice, it is determined to be in a crystallized state, and when not found, it is determined to be in an amorphous state.
[0067] In the B layer, the resin (b) is often in an amorphous state, and the amorphous resin (b) tends to exhibit low haze while also exhibiting low retardation. Therefore, from the viewpoint of exhibiting retardation in the multilayer optical film, it is preferable that the thickness of each B layer in the multilayer optical film is thin to a certain degree or more. The thickness of each B layer is preferably 10 μm or less, more preferably 9 μm or less. The lower limit of the thickness of the B layer is not particularly limited, but may be 3 μm or more from the viewpoint of effectively exhibiting solvent resistance.
[0068] [Resin (a): Amorphous polymer (a)] Examples of the amorphous polymer (a) which is a component of the resin (a) constituting the layer A include the same as the examples of the amorphous polymer (b2) described above. In the multilayer optical film of the present invention, the amorphous polymer (a) and the amorphous polymer (b2) may be the same or different.
[0069] Resin (a) may contain optional components in addition to the amorphous polymer (a). Examples of such optional components and their amounts are the same as those of resin (b). Resin (a) does not have a melting point because it is mainly composed of amorphous polymer (a). The fact that it does not have a melting point can be confirmed by the fact that no melting point is observed by the above-mentioned method for measuring the melting point of a polymer.
[0070] The glass transition temperature TgA of the resin (a) and the glass transition temperature TgB of the resin (b) satisfy the following formula (1). TgA-TgB≦20℃ (1) The value of TgA-TgB is 20°C or less, preferably 15°C or less. According to the present inventors' findings, when the value of TgA-TgB is equal to or less than the upper limit, it becomes possible to easily produce a multilayer optical film in a high quality state. Specifically, it is possible to effectively suppress undesirable phenomena such as the occurrence of thickness unevenness on a cooling roll when a resin is formed into a film by melt extrusion, and the occurrence of breakage when a film before stretching is subjected to a stretching process. Therefore, it is possible to realize a multilayer optical film that can be easily produced in a high quality state while enjoying the advantages of having a B layer on the surface layer, such as high solvent resistance.
[0071] The lower limit of the TgA-TgB value is not particularly limited, but can usually be set to at least -10° C., preferably at least -5° C. When the TgA-TgB value is at least the lower limit, the multilayer resin film can have both heat resistance and solvent resistance during use.
[0072] The glass transition temperature TgA of the resin (a) itself is not particularly limited, but from the viewpoint of increasing the heat resistance when the multilayer optical film is used, it is preferable that the TgA is high. On the other hand, from the viewpoint of ease of handling, it is preferable that the TgA is low to a certain degree. Specifically, the TgA is preferably 105°C or higher, more preferably 110°C or higher, and is preferably 145°C or lower, more preferably 140°C or lower. The glass transition temperature TgA of the resin (a) can be adjusted, for example, by appropriately selecting the type of the crystalline polymer (a). The glass transition temperature TgA of the resin (a) can be measured by the same method as the method for measuring the glass transition temperature of the polymer described above.
[0073] [A layer] The thickness of the A layer is not particularly limited, but is preferably at least a certain thickness from the viewpoint of effectively expressing the retardation of the multilayer optical film. The lower limit of the thickness of the A layer is preferably 10 μm or more, more preferably 20 μm or more. On the other hand, from the viewpoint of thinning the device equipped with the multilayer optical film, the upper limit of the thickness of the A layer is preferably 160 μm or less, more preferably 150 μm or less.
[0074] [Properties of multilayer optical films] The multilayer optical film of the present invention can have excellent solvent resistance. For example, the multilayer optical film can be a film that does not easily break even when n-hexane is dropped onto the bent portion of the bent multilayer optical film.
[0075] The multilayer optical film of the present invention can have excellent heat resistance by setting the glass transition temperature TgA of the resin (a) constituting the layer A within an appropriate range, thereby making it possible to suppress the change in retardation in a high-temperature environment and the increase in haze in a high-temperature environment.
[0076] The multilayer optical film can easily exhibit high birefringence in the A layer. The multilayer optical film can be made into a film that has high birefringence suitable for applications such as a retardation film, has excellent solvent resistance, and can be easily manufactured by combining the A layer and the B layer. The specific birefringence of the multilayer optical film is preferably 0.00200 or more, more preferably 0.00205 or more, and particularly preferably 0.00210 or more. There is no particular limit to the upper limit of the birefringence Δn, and it can be, for example, 0.01000 or less, 0.00800 or less, etc.
[0077] The multilayer optical film can have an in-plane retardation suitable for its application. For example, the in-plane retardation Re of the multilayer optical film at a measurement wavelength of 590 nm is preferably 30 nm or more, more preferably 40 nm or more, particularly preferably 50 nm or more, and is preferably 300 nm or less, more preferably 290 nm or less, particularly preferably 280 nm or less.
[0078] The multilayer optical film can have a thickness direction retardation suitable for its application. For example, the thickness direction retardation Rth of the multilayer optical film at a measurement wavelength of 590 nm is preferably 0 nm or more, more preferably 5 nm or more, particularly preferably 10 nm or more, and is preferably 300 nm or less, more preferably 250 nm or less, particularly preferably 200 nm or less.
[0079] The in-plane retardation and thickness direction retardation of the multilayer optical film can be measured by a phase difference meter ("AxoScanOPMF-1" manufactured by AXOMETRICS).
[0080] The multilayer optical film preferably has high transparency. The specific total light transmittance of the multilayer optical film is preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The total light transmittance of the film can be measured in the wavelength range of 400 nm to 700 nm using an ultraviolet-visible spectrometer.
[0081] The multilayer optical film preferably has a small haze. The haze of the multilayer optical film is preferably 2.0% or less, more preferably 1.0% or less, particularly preferably 0.5% or less, and ideally 0.0%.
[0082] The multilayer optical film may be a sheet-like film or a long film having a long shape.
[0083] The total thickness of the multilayer optical film can be appropriately set depending on the application of the multilayer optical film, but it is usually desirable that the thickness is thin from the viewpoint of thinning of a device including the multilayer optical film, etc. The specific thickness of the multilayer optical film is preferably 10 μm or more, more preferably 20 μm or more, and is preferably 160 μm or less, more preferably 150 μm or less.
[0084] The ratio of the thickness of layer A to the total thickness of layer B in the multilayer optical film can be appropriately adjusted so as to obtain desired optical performance and properties such as solvent resistance.
[0085] In the multilayer optical film, the layers are directly in contact with each other without the intervention of other layers such as the A layer, the B layer, and the adhesive layer, and a structure in which the layers are in close contact with each other and are in close contact with each other can be adopted. In particular, when the resin (a) contains an alicyclic structure-containing polymer as the amorphous polymer (a), and the resin (b) contains an alicyclic structure-containing polymer as one or both of the crystalline polymer (b1) and the amorphous polymer (b2), the affinity between them can be increased, and interlayer adhesion can be obtained without the intervention of other layers. The presence or absence of interlayer adhesion can be determined by a tear test under the conditions shown in the examples of the present application. When peeling is not visible at the interface between the layers at the tear of the sample torn in the tear test, it can be determined that there is interlayer adhesion, and when peeling is visible at the interface between the layers, it can be determined that there is no interlayer adhesion.
[0086] [Method of manufacturing multilayer optical film] The multilayer optical film of the present invention can be produced by a production method including the following steps (i) and (ii). Hereinafter, this production method will be described as a method for producing the multilayer optical film of the present invention. The method for producing the multilayer optical film of the present invention can also include the following step (iii) in addition to steps (i) and (ii). Step (i): preparing resin (a) and resin (b). Step (ii): A step of forming the resin (a) and the resin (b) to obtain a multilayer resin film. Step (iii): A step of stretching the multilayer resin film at a stretching temperature of TgA or higher.
[0087] The step (i) can be carried out by synthesizing a polymer by the above-mentioned production method for each polymer, and further mixing a plurality of polymers and optional components, if necessary.
[0088] The molding method in step (ii) is not particularly limited, and various known molding methods can be used. Examples of the molding method include extrusion molding, solution casting, and inflation molding. Among them, extrusion molding and solution casting are preferred, and extrusion molding is particularly preferred.
[0089] In the molding by extrusion molding, resin (a) and resin (b) can be co-extruded. Specifically, resin (a) and resin (b) in a molten state are co-extruded and discharged from an extrusion molding device capable of performing co-extrusion molding of two kinds and three layers, to form a layered molten resin, which is then cooled to perform co-extrusion molding. The melting temperature at the time of discharge is preferably (TgA+100)°C or higher, more preferably (TgA+110)°C or higher, while it can be preferably (TgA+180)°C or lower, more preferably (TgA+170)°C or lower. The cooling body with which the layered molten resin first comes into contact is not particularly limited, but a cast roll is usually used. The cast roll temperature is preferably TgA-15°C or higher, and preferably TgA+5°C or lower.
[0090] The multilayer resin film obtained in step (ii) can be used as it is as the multilayer optical film of the present invention as a product depending on the application. On the other hand, when a film having a large retardation is required as the multilayer optical film, step (iii) can be performed to impart a retardation to the multilayer film. This stretching orients the polymer molecules in the resin film, so that a multilayer optical film having preferable optical properties can be obtained. The stretching temperature during this stretching is preferably TgA°C or higher, more preferably TgA+5°C or higher, while it can be preferably TgA+40°C or lower, more preferably TgA+30°C or lower. By performing the stretching within such a temperature range, a desired retardation can be easily imparted.
[0091] On the other hand, from the viewpoint of suppressing the promotion of crystallization of the resin (b) in the B layer and suppressing an increase in haze, the stretching temperature may be set within a certain range relative to the glass transition temperature TgB and cold crystallization temperature TcB of the resin (b). Specifically, the stretching temperature is preferably TgB°C or higher, more preferably TgB+10°C or higher, and particularly preferably TgB+15°C or higher, while being preferably TcB-20°C or lower, more preferably TcB-25°C or lower, and particularly preferably TcB-30°C or lower.
[0092] The stretching ratio in step (iii) can be set according to the optical properties that the multilayer optical film should have. The specific stretching ratio is preferably greater than 1, more preferably 1.1 or more, particularly preferably 1.2 or more, and is preferably 5 or less, more preferably 4 or less, particularly preferably 3 or less. When performing biaxial stretching, it is preferable that the total stretching ratio, which is expressed as the product of the stretching ratio in one direction and the stretching ratio in the other direction, falls within the above range.
[0093] The stretching may be, for example, uniaxial stretching in which stretching is performed in one direction, or biaxial stretching in which stretching is performed in two non-parallel directions. The biaxial stretching may be simultaneous biaxial stretching in which stretching is performed in two directions at the same time, or sequential biaxial stretching in which stretching is performed in one direction and then in the other direction.
[0094] The method for producing a multilayer optical film may further include any step in combination with the above steps (i) to (iii). For example, the method for producing a multilayer optical film may include a step of preheating the resin film before stretching in step (iii). The preheating temperature is preferably at least "stretching temperature -40°C", more preferably at least "stretching temperature -30°C", and is preferably at most "stretching temperature +20°C", more preferably at most "stretching temperature +15°C".
[0095] Other examples of optional steps include trimming the multilayer optical film and subjecting the multilayer optical film to a surface treatment. EXAMPLES
[0096] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.
[0097] In the following description, the units "%" and "parts" are by weight unless otherwise specified. Furthermore, the operations described below were carried out in air at room temperature and normal pressure (23°C and 1 atm) unless otherwise specified.
[0098] [Evaluation method] (Method of measuring weight average molecular weight Mw and number average molecular weight Mn of polymer) The weight average molecular weight Mw and number average molecular weight Mn of the polymer were measured as polystyrene equivalent values using a gel permeation chromatography (GPC) system (Tosoh Corporation, "HLC-8320"). In the measurement, an H-type column (Tosoh Corporation) was used as the column, and tetrahydrofuran was used as the solvent. The temperature during the measurement was 40°C.
[0099] (Method for measuring hydrogenation rate of polymer) The hydrogenation rate of the polymer was measured using orthodichlorobenzene-d4 as a solvent at 145°C. 1 Measurements were performed by H-NMR.
[0100] (Measuring methods for melting point, glass transition temperature and cold crystallization temperature) The melting points and glass transition temperatures (TgA, TgB, etc.) of the resin and intermediates in the manufacturing process thereof, and the cold crystallization temperature TcB of the resin (b) were measured as follows. First, a sample to be measured, such as a resin, was melted by heating, and the melted sample was quenched with dry ice. Next, the glass transition temperature and cold crystallization temperature of the sample were measured at a heating rate of 10°C / min (heating mode) using a differential scanning calorimeter (DSC). The cold crystallization temperature was taken as the value at the top of the exothermic peak during the heating process.
[0101] (Method for measuring the ratio of racemo-dyads in polymers) The ratio of racemo-dyads in the polymer was determined as follows. 4 The inverse-gated decoupling method was applied to the polymer at 200°C using 13 C-NMR measurements were performed. 13 The results of C-NMR measurement showed that o-dichlorobenzene-d 4 Using the peak at 127.5 ppm as the reference shift, the signal at 43.35 ppm from the meso-dyad and the signal at 43.43 ppm from the racemo-dyad were identified. The ratio of the racemo-dyads in the polymer was calculated based on the intensity ratio of these signals.
[0102] (Method of measuring film thickness) The thickness of the entire film was measured using a contact thickness gauge (MITUTOYO, Code No. 543-390). The thickness of each layer was measured by cutting a cross section with a glass blade using a microtome and observing the cross section with a transmission microscope. When observation with a transmission microscope was difficult, a polarizing microscope was used with two polarizing plates in crossed Nicols (black arrangement) to observe the cross section.
[0103] (Method of measuring Re, Rth, Δn) The in-plane retardation Re and thickness retardation Rth of the film were measured using an "AxoScan OPMF-1" manufactured by AXOMETRICS. The measurements were performed at a wavelength of 590 nm. From the obtained Re value and the separately measured film thickness value, Δn was calculated according to the following formula. Δn=Re[nm] / d[nm]
[0104] (Solvent resistance test) The film to be evaluated was cut out to obtain a sample with dimensions of 5 cm x 2 cm in the longitudinal direction (the direction corresponding to the longitudinal direction when the film was long before being cut out) x width direction (the direction corresponding to the width direction when the film was long before being cut out).
[0105] The sample was bent so that the axial direction of bending (the cylindrical axial direction of the partially cylindrical shape generated by bending a flat sample, the same applies below) was the width direction of the sample and the longitudinal ends of the sample overlapped, and the longitudinal ends were held with clips (commercially available double clips (binder clips)), and the sample was placed in the shape shown in FIG. 1. In FIG. 1, sample 100 was held by clip 200 with its longitudinal ends 101 overlapping, resulting in the formation of bent portion 102. The position of holding by clip 200 was adjusted so that the diameter of bent portion 102 was 5 mm. Here, the diameter of bent portion 102 is the length indicated by arrow A1, which is the diameter of the bent portion in a direction Lh perpendicular to the extension direction Lv of longitudinal end 101 of sample 100.
[0106] Sample 100 was placed so that end 101 of sample 100 was on the bottom and top 103 was on the top, and a drop of n-hexane was dropped onto the position of top 103 using a dropper and held there for 30 seconds. After that, sample 100 was removed from clip 200, and sample 100 was evaluated according to the following evaluation criteria. Good: There are no cracks on the surface of the sample, or even if there are cracks, they do not penetrate through the thickness direction. Poor: A crack exists that penetrates the thickness direction of the sample (including cases where the sample is broken).
[0107] (Evaluation of film-forming properties) The thickness of the film to be evaluated was measured at 10 points at 3 cm intervals along the longitudinal direction (the direction corresponding to the longitudinal direction of the long film before cutting) using a contact thickness meter (MITUTOYO Co., Ltd., Code No. 543-390), and the difference between the maximum thickness and the minimum thickness was calculated. If the difference between the maximum thickness and the minimum thickness is 3 μm or less, the film formability is judged to be good.
[0108] (Confirmation of crystallization) TEM observation was performed under the following conditions, and when a spherulitic structure or difference in contrast was found in the observed slice, it was judged to be "crystallized." Pretreatment: Cut the cross section using a room temperature microtome (diamond knife), feed the sample 50 nm, and after sectioning, stain with Ru vapor for 40 seconds and 2 minutes. Six sections were observed. TEM equipment: Hitachi HT7700. Accelerating voltage: 100kV.
[0109] (Interlayer adhesion) The film to be evaluated was cut out to obtain a sample with dimensions of 150 cm x 50 cm in the longitudinal direction (the direction corresponding to the longitudinal direction of the long film before cutting) x width direction (the direction corresponding to the width direction of the long film before cutting). A slit of 75±1 mm was made in the longitudinal direction of the sample with a cutter knife from one end in the longitudinal direction, the position of the slit being within a range of 25±1 mm from the end in the width direction of the sample.
[0110] A tear test of the sample was performed using a test stand (manufactured by Imada Co., Ltd., product name "Motorized Test Stand MX-500N-L550-E") and a force gauge (manufactured by Imada Co., Ltd., product name "ZP-5N") attached to it. As shown in FIG. 2, the force gauge side gripper 310 and the test stand side gripper 320 each had a pair of flat gripping plates (311 and 312, and 321 and 322), and were shaped to grip the end of the sample with the inner gripping surfaces of the opposing plates. At the start of the measurement, the distance between the upper end of the test stand side gripper 320 and the lower end of the force gauge side gripper 310 was adjusted to 75 mm.
[0111] One end 410 of the sample 400 divided into two by the slit S was bent upward in an axial direction parallel to the sample width direction and held by the force gauge side holding tool 310. The other end 420 of the divided end of the sample 400 was bent downward in an axial direction parallel to the sample width direction and held by the test stand side holding tool 320. The length of each of the clamped ends was 30 mm. The ends 410 and 420 were located in the same vertical plane, and the positions of the holding tools 310 and 320 were adjusted so that their virtual center lines were aligned on the same line. The virtual center line of the end 410 is the center line of the sample in the width direction along the longitudinal direction of the sample at the part of the sample that is held in the virtual case where the sample is bent upward without being divided and held by the holding tool 310. The imaginary center line of end 420 is the center line of the sample in the width direction along the longitudinal direction of the sample at the gripped portion of the sample when the sample is bent downward without being divided and gripped by gripping tool 320.
[0112] While the gripping tool 320 was fixed, the gripping tool 310 was raised vertically upward at a moving speed of 200 mm / min to perform a tear test. After the sample was torn into two pieces, the sample was removed from the gripping tool and visually observed. If peeling was not visible at the interface between the layers at the tear in the sample, it was determined that there was interlayer adhesion, and if peeling was visible at the interface between the layers, it was determined that there was no interlayer adhesion.
[0113] (Haze measurement) The film was cut out to obtain a rectangular sample of 50 mm x 50 mm. The haze of the sample was measured using NDH-7000 (manufactured by Nippon Denshoku Co., Ltd.) in accordance with JIS K7361-1997.
[0114] [Production Example 1: Production of Resin (b)] A metallic pressure-resistant reactor was thoroughly dried and then purged with nitrogen. 154.5 parts of cyclohexane, 42.8 parts of a 70% cyclohexane solution of dicyclopentadiene (endo isomer content of 99% or more) (30 parts as dicyclopentadiene), and 1.9 parts of 1-hexene were added to the metallic pressure-resistant reactor and heated to 53°C.
[0115] 0.014 parts of tetrachlorotungsten phenylimide (tetrahydrofuran) complex was dissolved in 0.70 parts of toluene to prepare a solution. 0.061 parts of a 19% diethylaluminum ethoxide / n-hexane solution was added to this solution and stirred for 10 minutes to prepare a catalyst solution. This catalyst solution was added to a pressure-resistant reactor to start a ring-opening polymerization reaction. The reaction was then continued for 4 hours while maintaining the temperature at 53°C to obtain a solution of a ring-opened polymer of dicyclopentadiene. The number-average molecular weight (Mn) and weight-average molecular weight (Mw) of the obtained ring-opened polymer of dicyclopentadiene were 8,750 and 28,100, respectively, and the molecular weight distribution (Mw / Mn) calculated from these was 3.21.
[0116] To 200 parts of the obtained solution of the ring-opening polymer of dicyclopentadiene, 0.037 parts of 1,2-ethanediol was added as a terminator, heated to 60°C, and stirred for 1 hour to terminate the polymerization reaction. One part of a hydrotalcite-like compound (Kyowa Chemical Industry Co., Ltd.'s "Kyoward (registered trademark) 2000") was added, heated to 60°C, and stirred for 1 hour. Thereafter, 0.4 parts of a filter aid (Showa Chemical Industry Co., Ltd.'s "Radiolight (registered trademark) #1500") was added, and the adsorbent and the solution were filtered using a PP pleated cartridge filter (ADVANTEC Toyo Co., Ltd.'s "TCP-HX").
[0117] 100 parts of cyclohexane was added to 200 parts of the solution of the ring-opened polymer of dicyclopentadiene after filtration (polymer amount 30 parts), and 0.0043 parts of chlorohydridocarbonyltris(triphenylphosphine)ruthenium was added, and the hydrogenation reaction was carried out at a hydrogen pressure of 6 MPa and 180°C for 4 hours. As a result, a reaction solution containing a hydrogenated product of the ring-opened polymer of dicyclopentadiene as a crystalline polymer (b1) was obtained. The reaction solution was a slurry solution in which the hydrogenated product was precipitated.
[0118] The hydrogenated product and the solution contained in the reaction solution were separated using a centrifuge and dried under reduced pressure at 60°C for 24 hours to obtain 28.5 parts of a hydrogenated product of a crystalline ring-opening polymer of dicyclopentadiene. The hydrogenation rate of this hydrogenated product was 99% or more, the glass transition temperature (Tg) was 93°C, the melting point (Tm) was 266°C, and the ratio of racemo-dyads was 89%.
[0119] 100 parts of the obtained hydrogenated ring-opening polymer of dicyclopentadiene was mixed with 1.1 parts of an antioxidant (tetrakis [methylene-3- (3', 5'-di-t-butyl-4'-hydroxyphenyl) propionate] methane; "Irganox (registered trademark) 1010" manufactured by BASF Japan Ltd.), and then the mixture was put into a twin-screw extruder (product name "TEM-37B", manufactured by Toshiba Machine Co., Ltd.) equipped with four die holes having an inner diameter of 3 mm Φ. The mixture of the hydrogenated ring-opening polymer of dicyclopentadiene and the antioxidant was molded into a strand shape by hot melt extrusion molding, and then chopped with a strand cutter to obtain a pellet-shaped crystalline resin (b1). The operating conditions of the twin-screw extruder were as follows. The glass transition temperature TgB and cold crystallization temperature TcB of the obtained crystalline resin (b1) were measured. Barrel temperature setting: 270~280℃ Die temperature setting = 250℃ Screw speed: 145 rpm
[0120] Thereafter, resin (b2) (ZEONEX790R; manufactured by Zeon Corporation, glass transition temperature 163°C, no melting point was observed) was prepared as the amorphous polymer (b2), and was fed into a twin-screw kneading extruder (L / D=41, φ25mm) with a weight feeder so that the weight ratio of crystalline resin (b1): amorphous resin (b2) was 45:55. The mixture was formed into a strand shape by twin-screw kneading, and then chopped with a strand cutter to obtain a pellet-shaped crystalline resin (bI). The operating conditions of the twin-screw extruder were as follows. The glass transition temperature TgB and cold crystallization temperature TcB of the obtained crystalline resin (bI) were measured. The melting point of the crystalline resin (bI) was 263°C. Barrel temperature setting: 275~280℃ Die set temperature = 275℃ Screw speed = 200 rpm
[0121] [Production Example 2] A pellet-shaped crystalline resin (b-II) was obtained by the same procedure as in Production Example 1, except that the ratio of crystalline resin (b1) to amorphous resin (b2) was changed to crystalline resin (b1): amorphous resin (b2) = 35:65, and the glass transition temperature TgB and cold crystallization temperature TcB were measured. The melting point of the crystalline resin (b-II) was 263°C.
[0122] Example 1 (1-1. Step (1): Production of a multilayer resin film consisting of an amorphous resin (a) and a crystalline resin (b)) A double-flight type single-screw extruder (screw diameter D = 50 mm, ratio of screw length L to screw diameter D = 28) equipped with a leaf disk-shaped polymer filter with a mesh size of 3 μm was prepared. Amorphous resin (a) (ZEONEX690R; manufactured by Zeon Corporation; glass transition temperature 136 ° C, melting point not observed) was introduced into this single-screw extruder, melted, and fed to a single-layer die via a feed block for two-kind three-layer extrusion. "Two-kind three-layer" means that the number of layers contained in the film is three layers, and the types of resins forming these layers are two types. Resin (a) was introduced into the single-screw extruder through a hopper loaded in the single-screw extruder. The temperature of resin (a) at the extruder outlet was 280 ° C.
[0123] On the other hand, a single screw extruder (screw diameter D=50 mm, ratio of screw length L to screw diameter D L / D=30) equipped with a leaf disk-shaped polymer filter with a mesh size of 3 μm was prepared. The crystalline resin (bI) produced in Production Example 1 was introduced into this single screw extruder, melted, and fed to the single layer die via a feed block. The temperature of the resin (bI) at the extruder outlet was 280° C.
[0124] Thereafter, resin (a) and resin (bI) were extruded from a single-layer die in a molten state at 275°C to obtain a layered molten resin having three layers, in this order, a layer of resin (bI), a layer of resin (a), and a layer of resin (bI). The extruded layered molten resin was cast onto a cooling roll adjusted to a temperature of 120°C, edge pinning was performed on the roll, and the resin was transported and cooled to obtain a long multilayer resin film.
[0125] The obtained multilayer resin film was a two-kind three-layer film having a layer B of resin (bI), a layer A of resin (a), and a layer B of resin (bI) in that order in the thickness direction. The total thickness of the multilayer resin film was 136 μm. The thickness of each of the B layers was 8 μm, and the thickness of the A layer was 120 μm.
[0126] (1-2. Process (2): Heat stretching process) The multilayer resin film obtained in (1-1) was cut into a rectangular film measuring 130 mm x 130 mm, with each side of the rectangular film parallel to the length or width of the long multilayer resin film. The rectangular film was placed in a stretching machine (manufactured by Etoh Corporation), and each of the four sides was held by five clips, and the film was preheated at 150°C. Six minutes after the start of preheating, when the film temperature stabilized, the film temperature was maintained at 150°C, and the film was uniaxially stretched with fixed ends in the longitudinal direction (the direction corresponding to the longitudinal direction of the long film before cutting). The stretching ratio was 3 times, and the stretching speed was 7 mm / sec. Through this process, the multilayer resin film was heated and stretched to obtain a multilayer optical film.
[0127] For the obtained multilayer optical film, the haze, Re, Rth, and thickness d were measured, Δn was determined, and the interlayer adhesion, solvent resistance, film formability, and the presence or absence of crystallization were evaluated.
[0128] Example 2 A multilayer resin film and a multilayer optical film were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In step (1-1), the resin (b-II) obtained in Production Example 2 was used in place of the resin (bI). In order to obtain a retardation of about 250 nm after stretching, the rotation speed of the extruder screw was adjusted in step (1-1), and the thicknesses of each of the layers B, A, and B before stretching were changed to those shown in Table 1.
[0129] Comparative Example 1 A multilayer resin film and a multilayer optical film were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In step (1-1), the crystalline resin (b1) used in Production Example 1 was used as it was, instead of the resin (bI), without being mixed with the resin (b2). In order to obtain a retardation of about 250 nm after stretching, the rotation speed of the extruder screw was adjusted in step (1-1), and the thicknesses of each of the layers B, A, and B before stretching were changed to those shown in Table 1.
[0130] Comparative Example 2 A multilayer resin film and a multilayer optical film were obtained and evaluated by the same procedures as in Example 1, except for the following changes. In step (1-1), ZEONEX790R (manufactured by Zeon Corporation; TgA = 163°C; the same as the resin (b2) used in Production Example 1) was used as the amorphous resin (a) instead of ZEONEX690R. In order to obtain a retardation of about 250 nm after stretching, the rotation speed of the extruder screw was adjusted in step (1-1), and the thicknesses of each of the layers B, A, and B before stretching were changed to those shown in Table 1. The preheating and stretching temperatures were changed to 165°C to match resin (a).
[0131] Comparative Example 3 Except for the following changes, the same procedures as in Example 1 were carried out to obtain and evaluate a single-layer film of Layer A, which is the layer of resin (a), instead of the multilayer resin film, and an optical film obtained by stretching this film. In step (1-1), resin (bI) was not supplied to the feed block, and only resin (a) was supplied. In order to obtain a retardation of about 250 nm after stretching, the rotation speed of the screw of the extruder was adjusted in the step (1-1) and the thickness of the layer A before stretching was changed to the thickness shown in Table 1.
[0132] The outline and results of the examples and comparative examples are shown in Table 1.
[0133] [Table 1]
[0134] As is clear from the above results, compared to the comparative examples, the multilayer optical films of the examples of the present application can be high-quality optical films that have high solvent resistance due to layer B while also having desired physical properties such as low haze and low thickness unevenness. [Explanation of symbols]
[0135] 100: Sample 101: Sample longitudinal end 102: Sample bending part 103: Sample top 200: Clip 310: Force gauge side gripper 311: Flat plate for gripping 312: Flat plate for gripping 320: Measuring stand side gripper 321: Flat plate for gripping 322: Flat plate for gripping 400: Sample 410: End of sample 420: End of sample A1: Diameter of the bend Lh: A direction perpendicular to Lv Lv: Extension direction of the longitudinal end of the sample S: Slit
Claims
1. A multilayer optical film comprising a pair of B layers constituting surface layers on a front surface and a back surface, and an A layer located between the pair of B layers, The layer A is a layer of a resin (a) containing an amorphous polymer (a) having no melting point, The layer B is a layer of a resin (b) having a melting point, which contains a crystalline polymer (b1) having a melting point and an amorphous polymer (b2) not having a melting point, The resin (a) and the resin (b) satisfy the following formulas (1) to (3), TgA-TgB≦20℃ (1) 110℃<TgB<140℃ (2) 180℃<TcB<235℃ (3) where TgA is the glass transition temperature of resin (a), TgB is the glass transition temperature of resin (b), and TcB is the cold crystallization temperature of resin (b). Multilayer optical films.
2. The multilayer optical film of claim 1 , wherein the A layer and the B layer are in intimate contact with each other.
3. The multilayer optical film according to claim 1 or 2, wherein each of the B layers has a thickness of 10 μm or less.
4. The multilayer optical film of any one of claims 1 to 3, having a haze of 1% or less.
5. A method for producing the multilayer optical film according to any one of claims 1 to 4, comprising the steps of: preparing the resin (a) and the resin (b); A production method comprising a step of forming the resin (a) and the resin (b) to obtain a multilayer resin film.
6. The method for producing a multilayer optical film according to claim 5 , further comprising the step of stretching the multilayer resin film at a stretching temperature equal to or higher than TgA.
Citation Information
Patent Citations
Input circuit
JP1991230614A
Polymer composition
JP2002249645A
Cycloolefin-based polymer composition and molding material
JP2007016102A
Laminated film
JP2021054070A
Polarizing laminated film and laminated film
WO2013069666A1